(untitled) - Space Imaging, LLC (Colorado, U.S.A., 2003)
The product guide introduce the operation of the IKONOS satellite (1999) and the six levels of IKONOS imagery products.
Keywords: Astronomical instuments,Thiết bị thiên văn